Employers’ Feedback on Hospitality Management Graduates from Palawan State University: A Mixed-Methods Study - Sibulan, Kent Voices D.; Dela Cruz, Trisha Mae B.; Del Monte, Mylyn S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines employer feedback on the performance of Bachelor of Science in Hospitality Management (BSHM) graduates from Palawan State University’s Brooke’s Point campus. A mixed-methods approach using a descriptive research design was employed to explore employers’ perceptions of graduates’ soft and hard skills within the hospitality industry. The research was conducted across Puerto Princesa City, Coron, and Brooke’s Point in Palawan, with data collected through surveys and interviews from 20 employers in various hospitality sectors, including Front Office, Housekeeping, and Food & Beverage. Purposive sampling was used to select employers who had hired BSHM graduates between 2019 and 2024. The data were analyzed using frequency counts, percentages, and means. The findings revealed that BSHM graduates performed well in soft skills such as teamwork, adaptability, communication, and interpersonal skills, with employers expressing high levels of satisfaction. The graduates also demonstrated strong hard skills, including computer literacy, presentation, and writing abilities. However, areas for improvement were identified, including workplace ethics, confidence in managing complex tasks, exposure to international cuisines and standards, and proficiency in industry-specific software such as Property Management Systems (PMS) and Point of Sale (POS) systems. The study recommends enhancing practical experience across all hospitality departments and increasing exposure to international standards. It further suggests updating the BSHM curriculum to better align with industry needs, with a focus on global practices, technological literacy, and skill development. These findings offer valuable insights for academic institutions, employers, and future researchers.